Edutainment dalam Pengembangan Multiple Intelligences Teori Howard Gardner pada Anak Usia Dini (PIAUD IAIN Kudus, 2018)
There are nine intelligences proposed by Howard Gardner. Nine intelligences include: intelligence language, logical-mathematical, visual-spatial, bodily-kinesthetic, rhythmic-musical, intrapersonal, interpersonal, naturalistic and existential. When speaking of the intelligence then of course it's going to talk about a person's brain. In theory the brain, it is said that the brain will only absorb information if the brain is in a state of happy to get it. Then to condition it, teachers should make learning fun and humanizing learners. Appropriate learning models would improve intelligence learners. One model of learning that can be used to improve the intelligence of the learner is to use the model of edutainment. This article attempts to provide edutainment strategies in the use of the model to the increase of multiple intelligences of children.